Simulasi Pertolongan Pertama Manajemen Fraktur di SMP Islam Terpadu Al-Ghozali Jember - Ridla, Akhmad Zainur; Setioputro, Baskoro; Hakam, Mulia (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase students’ knowledge and skills in first aid for fractures at Al-Ghozali Integrated Islamic Middle School Jember. The method used in carrying out community service activities regarding first aid to fracture victims involved lectures, discussions, and simulations related to handling fracture victims. The fracture Knowledge Questionnaire evaluated students’ knowledge about fracture first aid. The results of the Wilcoxon test from the pre-test and post-test had a significance value of < 0.05, meaning there are differences in students’ knowledge before and after health education about first aid trauma management fractures. Fracture education and simulation improved students’ ability to identify and perform appropriate fracture first aid.